Political Conflict and Political Ideas in Twelfth-Century Denmark - Kjær, Lars (Viking and Medieval Scandinavia, 2017)
Abstract This article investigates the nature of political life and conflict in medieval Denmark, focusing on the case of the rebellion against King Niels between 1131 and 1135. The article engages with previous scholarship that has identified the basis of the rebellion, and the governing feature of political life in the period, as the material interests of the competing kin-networks. Through an investigation of both the documentary and the narrative sources for the conflict, the reigns of King Niels and his successor Erik II Emune, the leader of the rebellion, this article argues that in fact political and religious principles were much more important. Building on this it argues that we need to pay much more attention to the stated principles of political actors as found in the contemporary sources and the way these enabled aristocrats and would-be kings to mobilize support.